Surface density measured using 3-m-deep firn cores over Blåskimen Island, Dronning Maud Land - Goel, Vikram; Matsuoka, Kenichi (Norwegian Polar Institute, 2017)
Dataset provides depth averaged density obtained from 3-m-deep shallow cores, drilled over 14 sites spread across Blåskimen Island ice rise in western Dronning Maud Land. This data is used for determining the spatial variability of surface density over the ice rise. It was collected during 2014 and is provided in a MATLAB (.mat) file format. IRD_surface_density.mat includes a struct-class variable including – • ‘lat’ and ‘lon’ arrays with latitude and longitudes in decimal degrees • ‘x’ and ‘y’ arrays with coordinates in a polar stereographic projection parallel to 71° S (EPSG 3031)., and ‘z’ shows elevations above the WGS84 ellipsoid. All are in the unit of meters. • ‘rho’ with surface density in kg m-3 See the following manuscript for further details: Goel, V., Brown, J., and Matsuoka, K.: Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica, The Cryosphere Discuss., https://doi.org/10.5194/tc-2017-61, in review, 2017.